IMPROVING SCIENCE LEARNING OUTCOMES ON ANIMAL LIFE CYCLE MATERIAL THROUGH PICTURE CARDS FOR GRADE IV ELEMENTARY SCHOOL STUDENTS - Khania Dwi Kayzahra; Nusrotul Maula; Ade Rika Rachim; Lutfi Yusri; Mawardi (Journal Informatic, Education and Management (JIEM), 2026)
This study was conducted to improve students' learning outcomes in the Natural and Social Sciences (IPAS) subject on the topic of animal life cycles through the use of picture card media. This research employed Classroom Action Research (CAR), which was carried out in three cycles consisting of planning, action, observation, and reflection. Data were collected through observation, learning achievement tests, and documentation, then analyzed using descriptive quantitative and qualitative methods. The results showed that the use of picture card media improved students' learning outcomes. Learning mastery increased from 33.3% in Cycle I to 83.3% in Cycle II and reached 100% in Cycle III. In addition, students became more active and enthusiastic during the learning process. Therefore, picture card media is effective in improving students' learning outcomes on the topic of animal life cycles in Grade IV elementary school.